Prognostic value of indoleamine 2, 3-dioxygenase-1 expression in glial tumors - Kaya, Munir; Aksoy, Asude; Artas, Gokhan; Kaplan, Metin (Literatura Medica, 2023)
Background and purpose - Gliomas are the most common primary malignant central nervous system tumors in adults, exhibiting a poor prognosis. Indoleamine 2, 3-dioxygenase-1 (IDO-1) has important functions in cancer immunotherapy due to its role in escaping cancer cells from the immune system. In this study we purposed to evaluate the correlation between IDO-1 expression and clinicopathological parameters in gliomas, and whether IDO-1 can be a prognostic marker. Methods - n=75 patients in total, n=25 patients with low grade glial tumors (LGG, grade 1-2), n=25 patients with high grade glial tumors (HGG, grade 3-4), and n=25 persons with normal brain tissue as control group were included in this study. IDO-1 expression was categorized by using immunohistochemical staining in biopsy specimens as high (H) and low (L) groups among the patients with gliomas. We used a 95% percent confidence interval and p <0.05 to analyze the association between the degree of IDO-1 expression, clinicopathological characteristics, and survival rates in glioma patients. Results - In HGG, IDO-1 levels were higher than in control brain tissue and LGG (p<0.001). The mean overall survival (OS) was longer in the L-IDO-1 group (64.53 +/- 3.34) in months (95% CI: 57.969-71.098) compared to the H-IDO-1 group (43.74 +/- 4.36) in months, (95% CI: 35.218-52.330) (p< 0.05). Conclusion - IDO-1 expression is an independent prognostic biomarker to predict OS and progression in HGG. IDO-1 can be evaluated as an alternative instrument for precision medicine in the treatment of gliomas.
Az indolamin 2, 3-dioxigenáz-1 expressziójának prognosztikai értéke gliadaganatokban
Keywords: glioma; indoleamine 2,3-dioxygenase1; prognosis; survival